Green Sorbitol- and Isosorbide-Based Flame Retardants for Cotton Fabrics - David De Smet (MDPI AG, 2021)
Flame retardancy is often required in various textile applications. Halogenated flame retardants (FR) are commonly used since they have good FR performance. Several of these components are listed under REACH. Halogen-free FR compounds have been developed as alternatives. So far, not many biobased FR have made it to the market and are being applied in the textile sector, leaving great opportunities since biobased products are experiencing a renaissance. In this study, renewable FR based on sorbitol and isosorbide were synthesised. The reaction was performed in the melt. The resulting biobased FR were characterised via FT-IR, thermogravimetric analysis (TGA) and X-ray fluorescence (XRF). Cotton fabrics functionalized with the developed biobased FR passed ISO 15025 FR test. After washing, the FR properties of the fabrics decreased (longer afterflame and afterglow time) but still complied with ISO 15025, indicating the biobased FR were semi-permanent. The amount of residue of modified sorbitol and isosorbide measured at 600 °C in air was 31% and 27%, respectively. Cotton treated with biobased modified FR showed no ignition during cone calorimetry experiments, indicating a flame retardancy. Furthermore, a charring of the FR containing samples was observed by means of cone calorimetry and TGA measurements.